Catastrophe insurance market in the Caribbean region : market failures and recommendations for public sector interventions : main report (World Bank WashingtonUS, 2002)
Assesses the vulnerability of countries in the Caribbean region to catastrophic shocks and the impact of these shocks on household and aggregate welfare. Evaluates the efficiency of the Caribbean catastrophic insurance industry in transferring catastrophe risks. Outlines a set of recommendations for public sector interventions.
Contents: v.1. Main report